2021
DOI: 10.3748/wjg.v27.i14.1362
|View full text |Cite
|
Sign up to set email alerts
|

How far along are we in revealing the connection between metformin and colorectal cancer?

Abstract: Colorectal cancer (CRC) is among the most prevalent cancers worldwide, and its prevention and reduction of incidence is imperative. The presence of diabetes has been associated with a 30% increased risk of CRC, likely through the mechanism of hyperinsulinemia, which promotes tumorigenesis via the insulin receptor in the epithelium or by insulin-like growth factor pathways, inflammation, or adipokines, inducing cancer cell proliferation and cancer spread. Metformin, the first-line agent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 50 publications
2
25
0
3
Order By: Relevance
“…Type II diabetes patients have been shown to suffer from increased risk of developing CRC (Berkovic et al ., 2021). Mounting evidence suggests that the first line type II diabetes drug, metformin, could be beneficial in preventing the CRC development and improving the cancer prognosis (Berkovic et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type II diabetes patients have been shown to suffer from increased risk of developing CRC (Berkovic et al ., 2021). Mounting evidence suggests that the first line type II diabetes drug, metformin, could be beneficial in preventing the CRC development and improving the cancer prognosis (Berkovic et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Type II diabetes patients have been shown to suffer from increased risk of developing CRC (Berkovic et al ., 2021). Mounting evidence suggests that the first line type II diabetes drug, metformin, could be beneficial in preventing the CRC development and improving the cancer prognosis (Berkovic et al ., 2021). The MoA of metformin is pleiotropic, affecting both whole organism and cellular level (Pernicova and Korbonits, 2014; Rena et al ., 2017), but not yet completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, an oral anti-diabetic medication used for type 2 diabetes mellitus, is a biguanide drug that increases insulin sensitivity, decreases intestinal absorption of glucose, and decreases its production by the liver [100]. Previous studies have shown a protective effect of metformin in CRC risk and prognosis [101,102]. The current understanding is that metformin inhibits the mammalian target of rapamycin (mTOR) pathway which plays a central role in CRC cell growth and proliferation [49].…”
Section: Anti-diabetic Drugsmentioning
confidence: 99%
“…Diabetes mellitus (DM) itself is a well-established risk factor and/or comorbidity for several pathologies seen in surgical wards, such as gastrointestinal malignancy, abdominal, and/or peripheral artery disease, likely with amputation and obesity with bariatric surgery ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%